REVISION OF THE OSTRACODE SUBGENUS PALEOBLITACYTHEREIS BENSON, 1977 (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
The genus Oblitacythereis, type species Oblitacythereis (Oblitacythereis) mediterranea Benson, 1977, and the subgenera Oblitacythereis and Paleoblitacythereis are well defined by Benson (1977), who designated Carinocythereis ruggierii Russo, 1966 as type species of Paleoblitacythereis. The specimens figured and described as Carinocythereis ruggierii by Benson (1977), however, clearly differ from Russo's species, and coincide well with Oblitacythereis sp. 3 Russo & Bossio, 1976, as stated by Bonaduce & Russo (1985). As a consequence of this misidentification the subgenus Paleoblitacythereis is subject to uncertainty and potential instability. The type species designated by Benson should be considered as a new nominal species and Carinocythereis ruggierii Russo, which actually belongs to Paleoblitacythereis, should be revised. The study of well-preserved specimens from some Miocene formations in southern Italy prompts the author to propose herein a systematic revision of the Italian representatives of the subgenus Paleoblitacythereis. Three species are discussed. These are: Oblitacythereis (Paleoblitacythereis) ruggierii (Russo, 1966), Oblitacythereis (Paleoblitacythereis) bossioi n. sp. ( = Oblitacythereis sp. 3 Russo & Bossio, 1976), here proposed as the new nominal type species of Paleoblitacythereis and, finally, Oblitacythereis (Paleoblitacythereis) apula n. sp., described as new. The systematic notes of each species are given with the bio-chronostratigraphical distribution resulting from the present study together with some palaeoecological remarks.